Klonet: a network emulation platform for the technology innovation - Jingzhao XIE; Wei SHAN; Chang XIAO; Tie MA; Li CHEN; Hongfang YU; Gang SUN (Dianxin kexue)
The innovations of key technologies enable and promote the future development of networks and the network industry.Therefore, there is an urgent need for a network experimental platform that can easily and quickly verify innovative network technologies, so asto effectively lower the innovation barriers and promote innovations.By analyzing the advantages of network emulation technology in network experiments and combining the demand of network technology innovation for network experiment platform, a network emulation experiment platform Klonet for network technology innovation was proposed.The platform can flexibly expand the scale of the network, emulate the network in all perspectives, manage the emulated network in a fine-grained manner, and thus ease the workflow of network experimentation.The experimental method on Klonet was described and the ability of Klonet to support network technology innovation was verified based on two specific use cases.